The Role of Marketing Strategy to Increase Brand Trust in the "Pospay" at PT POS Indonesia Malang - Muhammad Ahza Safaraz; Sukaris sukaris (INNOVATION RESEARCH JOURNAL, 2023)
Pospay application is growing quite rapidly both internally and externally, so it requires several marketing strategies so that it can influence Brand Trust from the Pospay Application. So, good integrated financial services are needed so that PT Pos Indonesia (Persero) can carry out transactions where previously one person could only carry out one transaction, but PT. Pos has carried out innovations that can provide benefits to society. In this case PT. Pos presents an application offered to consumers to facilitate transactions. Here the application is called POSPAY which aims to provide easy financial services to public which is fixed relevant with changing times in the digital era. The main goal is to shorten time by making several payments at just one time. This study uses a qualitative method, technique data collection using direct observation and interviews with Managers/Staff Financial Services. This observation was carried out in a flexible discussion. The subjects and place of this research are employees of PT Pos Indonesia (Persero) Regional 5 Malang. From the results of observations and interviews, the author can conclude that marketing strategies are able to increase public trust in PT. Pos Indonesia through the Pospay application, such as holding workshop events, sponsoring various events related to transactions, and collaborating with various products outside the company.